APLIKASI ALGORITMA DIJKSTRA UNTUK MENENTUKAN RUTE TERPENDEK DARI KAMPUS A KE B UIN RADEN FATAH - SAPUTRAMA, RENDI; HARTATIANA, HARTATIANA (E-Jurnal Matematika; Vol 10 No 3 (2021), 2021)
Finding the shortest direction is one of the options that have been considered while traveling. One of the problems that occur for lecturers, staff, and students of UIN Raden Fatah is determining the shortest direction from Campus A to B. The application of graph theory by using Dijkstra's Algorithm becomes a solution for this problem. This algorithm has the advantage to minimize the expense of the costs by finding the shortest route from starting point to the destination. This study is applied research. The study will discuss the determination of the origin and destination end-point, traverse route, the calculation of the weight distance, analyzes the Dijkstra's iteration to determine the shortest route, and conclusion. As the result, the land route becomes the shortest route option from UIN Raden Fatah Campus A to B. The directed graph of the route represents the location as point, the road as the side, and distance as weight. The result shows that the route distance is 6.94 km using Dijkstra's Algorithm.